Pengaruh Metode Pembelajaran Cooperative Integretet Reading And Composition Terhadap Peningkatan Reasoning Ability Pembelajaran Fiqih Pada Siswa Kelas VIII MTs YASPEND Muslim Pematang Tengah Kec. Tanjung Pura - Muhammad Khadafi, M. Yusuf Abdullah, Khairuddin YM (Journal of Educational Research and Humaniora (JERH), 2023)
The background of this research is that based on the identification carried out by the researchers at the research location, namely: The learning that has been carried out so far in class VIII of MTs Yaspend Muslim specifically for Fiqh subjects does not emphasize learning by providing direct learning experiences through the development of process skills, scientific attitudes and lack of developing reasoning. This causes the low reasoning ability of students. The objectives of this research are: To determine the effect of the cooperative learning method integretet reading and composition on increasing reasoning in learning fiqh students in class VIII MTs Yaspend Muslim. The type of research used in this study is a quantitative research method. In this study the form of the instrument used is in the form of a questionnaire using a Likert scale attitude that has been modified with the following assessments: often scores 3, Rarely scores 2, and Never scores 1. The results of this study are: The results of hypothesis testing are also carried out independently. partial with the significance or the effect of the independent variable on the dependent variable that, the tcount (partial) for the cooperative integret reading and composition learning method is 2,672 with a significance level of 0.01, the cooperative integrete reading and composition learning method variable has a positive and significant effect on increasing reasoning Students with a value of tcount (2.672) > ttable (2.021) and a significant value (0.01) <0.05 indicates that the cooperative integretet reading and composition learning method has a positive and significant effect on the improvement of students' reasoning. This can be seen with a significant value of 0.01 which is smaller than = 0.05. The cooperative integret reading and composition learning method will be able to improve students' reasoning because the better and better the cooperative integrete reading and composition learning method made by the teacher, students will get an increase in affective, cognitive, and psychomotor aspects in the classroom. Students will also look more active and critical, this is what causes the positive effect of the cooperative integrated reading and composition learning method on the improvement of students' reasoning.